Autopercepção de saúde, bem-estar e satisfação global com a vida de professores do Rio Grande do Sul - Civa, Daniela (2022)
The role of the teacher involves a huge contingent of responsibilities and challenges, which are often beyond the act of teaching and all the social ills, are part of this context. The work environment can have an impact on the mental health of teachers, and lead to the illness of these professionals. With the emergence of the pandemic, caused by Covid-19, the situation of total blockade required a change from traditional to online education, generating an increase in work, greater than usual, which can cause implications for the mental health of teachers, and affect their well-being and self-perception of health. In view of these facts, this dissertation aimed to evaluate the self-perception of health, well-being, and overall satisfaction with life among teachers in Rio Grande do Sul. This was a cross-sectional, exploratory descriptive study, with a quantitative approach, carried out from November 2020 to May 2021. Subproject of the integrative project, umbrella type, entitled "Gerontological education as a strategy to promote multigenerational interaction for healthy living and aging", approved by the Research Ethics Committee of the University of Passo Fundo under Opinion No. 467.889. The sample was made up of 371 teachers working at different levels of education in the state of Rio Grande do Sul, who agreed to participate voluntarily in the study by signing the informed consent form. The selection of participants was not probabilistic, by convenience, through the Virtual Snowball technique. At the time, an online questionnaire, developed in Google Forms, was applied. Quantitative analysis was performed using the Statistical Package for the Social Sciences (SPSS - v. 23) and Jamovi (statistical software). The significance level adopted for the statistical tests was 5%. The results are presented in two scientific papers, which constitute this dissertation. The first one entitled "Repercussion of health on life satisfaction of teachers from Rio Grande do Sul", in which the main result showed that regardless of the life conditions that teachers face, their health is primordial. The second, entitled "Professors of graduation and the use of medication for anxiety, physical inactivity and workload in the pandemic period", brought that regardless of the level of physical activity and workload they have, they are not risk factors for the use of medication for anxiety, as well as the practice of physical activity is not shown as a protective factor for the use of medication.